Characteristics of Rapid Response Calls in the United States: An Analysis of the First 402, 023 Adult Cases From the Get With the Guidelines Resuscitation-Medical Emergency Team Registry. Issue 10 (October 2019) - Lyons, Patrick G.; Edelson, Dana P.; Carey, Kyle A.; Twu, Nicole M.; Chan, Paul S.; Peberdy, Mary Ann; Praestgaard, Amy; Churpek, Matthew M.
Abstract : Objectives: To characterize the rapid response team activations, and the patients receiving them, in the American Heart Association-sponsored Get With The Guidelines Resuscitation-Medical Emergency Team cohort between 2005 and 2015. Design: Retrospective multicenter cohort study. Setting: Three hundred sixty U.S. hospitals. Patients: Consecutive adult patients experiencing rapid response team activation. Interventions: Rapid response team activation. Measurements and Main Results: The cohort included 402, 023 rapid response team activations from 347, 401 unique healthcare encounters. Respiratory triggers (38.0%) and cardiac triggers (37.4%) were most common. The most frequent interventions—pulse oximetry (66.5%), other monitoring (59.6%), and supplemental oxygen (62.0%)—were noninvasive. Fluids were the most common medication ordered (19.3%), but new antibiotic orders were rare (1.2%). More than 10% of rapid response teams resulted in code status changes. Hospital mortality was over 14% and increased with subsequent rapid response activations. Conclusions: Although patients requiring rapid response team activation have high inpatient mortality, most rapid response team activations involve relatively few interventions, which may limit these teams' ability to improve patient outcomes. Abstract : Supplemental Digital Content is available in the text.